A new CMOS differential current-mode AGC on the division operation based. Issue 11 (November 2015) - Bozomitu, Radu Gabriel; Cojan, Neculai
Abstract: A new CMOS differential current-mode AGC on the division operation based is presented. The operation principle consists in detection of both positive and negative envelopes of the differential input signal cycles, respectively. The output signal with constant magnitude is obtained by dividing the differential input signal to the difference between the positive and negative detected envelopes. The new current-mode architecture of the proposed AGC (composed only by an envelope detector and a divider stage) diminishes significantly the settling time, the circuit complexity and the power consumption. The circuit yields an input dynamic range of 15 dB and provides a constant magnitude output signal in the frequency range from 10 MHz to 70 MHz. The current consumption is 5 mA from a single 3.3 V supply voltage. The simulations performed in 0.13 µm CMOS process confirm the theoretically obtained results.